Organization of the motor neuron somata of geniohyoid and infrahyoid muscles in the medulla oblongata and spinal cord of rat: A horseradish peroxidase study / Aimi Nadia Razlan - Razlan, Aimi Nadia (2017)
Geniohyoid and infrahyoid muscles are important muscles of the neck because they are involved in the process of swallowing. The organization of their motoneurons has been studied by many investigators in rat and many other experimental animals but their results are not in agreement with each other even in the same species including rat. This prompted the present investigation. Thirty Sprague-Dawley rats were used in the study. The study was performed in medulla oblongata and upper cervical segments of spinal cord by retrograde transport of horseradish peroxidase (HRP) after its injection into geniohyoid and infrahyoid muscles using tetramethylbenzidine (TMB)- HRP method. The sections were examined to identify HRP-labelled neuron somata. Reconstruction of cell groups containing HRP-labelled neuron somaia was made. HRP-labelled neuron somata were organized as follows on the experimental (right) side: (1) Geniohyoid motoneurons: In rostral two thirds of closed part of medulla oblongata (MO) they were located in the ventral part of the main hypoglossal nucleus; in the caudal third of closed part of MO, they were in ventrolateral subnucleus. At spinomedullary junction (SMJ) they were in dorsomedial part of ventral grey column; a few were also seen scattered on right side of central canal and among the corticospinal fibres after pyramidal decussation. (2) Thyrohyoid motoneurons were found in dorsomedial part of right ventral grey column at SMJ and in dorsomedial column of right ventral grey column at C-l (first cervical segment). (3 & 4) Sternohyoid and sternothyroid motoneurons: At SMJ they were present in the region ventral or ventrolateral to the central canal and in the dorsomedial part of the right ventral grey column. At C-l and rostral half of C-2, they were located in dorsomedial column of right ventral grey column. In caudal half of C-2 and whole length of C-3, they were located in dorsomedial and ventrolateral columns of right ventral grey column. (5) Omohyoid motoneurons: At SMJ, they were observed in dorsomedial part of the right ventral grey column. At C-l, they were observed in the dorsomedial column of right ventral grey column. In C-2 and C-3, they were observed in dorsomedial and ventrolateral columns of right ventral grey column. Our results indicate that the motor neuron somata of geniohyoid muscle were organized in a group located in the medulla oblongata and at the SMJ, whereas, the motor neuron somata of infrahyoid muscles were organized in groups located at the SMJ and the ventral grey column of the cervical spinal cord.